Prosocial behavior and incentives: Evidence from field experiments in rural Mexico and Tanzania - Kerr J; Vardhan M; Jindal R (Elsevier, 2012)
Incentive-based schemes for natural resource conservation are based on the premise that offering payments to groups of land users will motivate them to organize collectively to provide environmental services. In contrast, research from behavioral economics shows that introducing monetary incentives can undermine collective action that is motivated by social norms. In such a case payment could have perverse impacts. In view of this dichotomy, we conducted choice and field experiments in rural Mexico and Tanzania to test the response of prosocial behavior to incentives. The field experiments involved voluntary participation in real communal tasks under different incentive structures. Findings suggest that payments help raise participation where people are otherwise uninterested, but that participation in communal tasks can be high irrespective of the incentive if social norms favoring participation are present. In Tanzania, high individual payments do not undermine participation although they appear to reduce people's satisfaction from the task relative to when there is no payment. In Mexico, group payments made through village authorities yield lower participation where people distrust leaders. Challenges to conducting field experiments in our research settings limit what we can conclude from our work, but the findings raise important points and suggest areas for further research.